STRATEGI KESANTUNAN OLEH WARGANET PADA UNGGAHAN INSTAGRAM TERKAIT KEBIJAKAN PEMERINTAH MENGENAI TES PCR - I Made Astu Mahayana; Dewa Ayu Dyah Pertiwi Putri; I Gede Sandi Haris Saskara (Prasasti: Journal of Linguistics)
This study aims to analyze the impoliteness strategies or those used by netizens on Instagram uploads related to government policies regarding PCR tests. This research was conducted because according to a survey conducted by the Digital Civility Index (DCI), Indonesian netizens were ranked first as disrespectful netizens in Southeast Asia. One of the causes of the emergence of impoliteness is caused by government policies that are not in favor of the people in terms of making decisions during the pandemic, one of which is the policy of implementing PCR. Therefore, this research is considered interesting to do. This research is a qualitative type of research using a descriptive approach. The data source of this research is the netizen's comments on Instagram uploads that discuss government policies related to PCR tests. In collecting data, additional instruments were used, namely gadgets, notebooks, and stationery. In addition, the data from this study were obtained from netizens' comments on Instagram social media uploads related to government policies regarding PCR tests. Through this research, it was found that in three Instagram uploads regarding government policies related to the PCR test, they contained several impolite strategies, 1) Bald On Record Impoliteness; 2) Positive Impoliteness; 3) Sarcasm/Mock Impoliteness; and 4) Multiple Impoliteness. Among the four impoliteness strategies, negative impoliteness is the dominant strategy used by netizens in the comment’s column. This shows that many people are disappointed and dissatisfied with the government's new policy regarding PCR.